The Curse of Expertise: When More Knowledge Leads to Miscalibrated Explanatory Insight. (15th September 2015) - Fisher, Matthew; Keil, Frank C.
Abstract: Does expertise within a domain of knowledge predict accurate self‐assessment of the ability to explain topics in that domain? We find that expertise increases confidence in the ability to explain a wide variety of phenomena. However, this confidence is unwarranted; after actually offering full explanations, people are surprised by the limitations in their understanding. For passive expertise (familiar topics), miscalibration is moderated by education; those with more education are accurate in their self‐assessments (Experiment 1). But when those with more education consider topics related to their area of concentrated study (college major), they also display an illusion of understanding (Experiment 2). This "curse of expertise" is explained by a failure to recognize the amount of detailed information that had been forgotten (Experiment 3). While expertise can sometimes lead to accurate self‐knowledge, it can also create illusions of competence.